India-China : Forging ‘Development Partnership’? - Suryanarayana, P. S. (2018)
China will be happy to have partners as it faces the United States in the emerging global trade war. With India seeking to break out of its geopolitical trap, there seems to be some room for a new ‘sense’ of Sino-Indian neighbourliness.